Phenotypic characterisation of Candida albicans mutants with deletions of arachidonic acid responsive genes - Motaung, Thabiso Eric (University of the Free State, 2015)
Candida albicans is a permanent resident of the healthy microbiome of humans. It co-inhabits the host micro-environment with trillions of species which make up the complete microbiota. Host parameters such as nutrient availability, CO2, and temperature as well as pH fluctuations are some of the key contributory elements to C. albicans phenotypic attributes and virulence. In this study, our analysis was based on arachidonic acid (AA), a polyunsaturated fatty acid, as an inducer of a genome wide transcriptional response. Arachidonic acid is a precursor of prostaglandins (PGs) such as PGE2 which can act on prostanoid receptors and potentially alter important biological functions. Since AA is available in the host, it is of great importance to understand the response of pathogenic yeasts to AA and how this interaction contributes to clinical infections. We analyzed genes up-regulated during AA exposure of C. albicans biofilms. Three mutants, two disrupted for membrane-bound proteins (ABC pheromone exporter transport, Hst6p, and amino acid sensor, Ssy1p) and ORF19.4612 (uncharacterized) were analyzed using phenotypic microarrays (PMs). Additional roles of Hst6p were uncovered in this study, one of which is linked to its up-regulation in the presence of AA. The PM data suggests that Hst6p is required for stress protection and conventional phenotypic screens confirmed this. ΔΔhst6 was found to be sensitive to osmotic, oxidative, cell wall and heavy metal stress. Because AA can induce sensitivity to stress, our phenotypic data suggest that HST6 was up-regulated during AA exposure, to respond to stress. In addition to HST6, other ABC transport genes, also important in stress, were up-regulated. Other groups have recently discovered the role of these proteins in stress in higher organisms such as humans, suggesting that the ABC-stress response system is widely conserved. Another function of Hst6p was suppression of hyphal formation in conditions replete with nitrogen sources. ΔΔhst6 was filamentous under these conditions. In addition, ΔΔhst6 formed highly wrinkled colonies with filamentous borders, whose cells were filamentous, under nitrosative stress. Therefore, our data supports the fact that Hst6p is expressed in all the cell types in C. albicans and has a more generic role as opposed to pheromone export alone. Analysis of phenotypes also revealed additional functions of the amino acid sensor, Ssy1p. According to literature, Ssy1p activates cleavage of Stp1p and Stp2p in response to lower pH and poor nutrient availability. In turn, these proteins activate amino acid permeases, Mep1p and Mep2p, required for pH neutralization and yeast-hyphal transition respectively. We found that under stressful conditions, Ssy1p results in differential stress response. For instance, while the wild type strain cells were inflated, cells of ΔΔssy1 grew normally on high ammonium concentrations and in the presence of nitrosative stress. In addition, ΔΔssy1 was resistant to osmotic and cell wall stress. Furthermore, ΔΔssy1 was sensitive to heat stress at 37 °C and 42 °C. Since AA conversion to PGE2 was conducted at 37 °C, and this fatty acid results in predisposition to stress which may affect membrane fluidity, we argue that SSY1 was up-regulated in response to heat stress. Although the microarray data failed to reveal genes directly involved in PGE2 production, the analysis of the white-gray-opaque-like (WGOL) switching, suggest that up-regulation of ORF19.4612 was necessary for rough pink (RP) cell formation and conversion of AA into PGE2. At 37 °C in RPMI-1640 medium, RP cells of the wild type strain produce significantly more PGE2 from AA. Δorf19.4612 is defective in RP cell formation after 3 days on conditions similar to those of RPMI-1640 medium. Since ORF19.4612 was expressed after 48 h at 37 °C, is therefore not only implicated in WGOL, but also in PGE2 production.

Candida albicans is ‘n permanente lid van die mikrobioom van gesonde mense. Dit deel die gasheer se mikro-omgewings met triljoene ander spesies wat saam deel uit maak van die totale microbiota. Toestande in die gasheer soos beskikbaaarheid van voedingstowwe, CO2, en temperatuur asook veranderings in pH is sommige van die sleutelelemente wat bydrae tot C. albicans se fenotipiese eienskappe en virulensie. In Ons analise in hierdie studie is gebaseer op arachidoonsuur (AS), ‘n polionversadigde vetsuur, as induseerder van ‘n genoomwye transkripsionele respons. Arachidoonsuur is ‘n voorloper van prostaglandiene (PGe) soos PGE2 wat inwerk op prostanoïedreseptore en potensiëel belangrike biologiese funksies kan beïnvloed. Aangesien AS in die gasheer beskikbaar is, is dit belangrik om die response van patogene giste op AS en hoe hierdie interaksie bydra tot kliniese infeksies te verstaan. Ons het gene wat opgereguleer is gedurende blootstelling van C. albicans biofilms aan AS, geanaliseer. Drie mutante, waarvan twee delesies van membraangebonde proteïene (ABC feromooneksportproteïen, Hst6p, end aminosuursensor, Ssy1p) en ORF19.4612 (ongekarakteriseerd) is geanaliseer m.b.v. fenotipiese “microarrays”. Addisionele funksies vir Hst6p is in hierdie studie ontdek. een daarvan is gekoppel aan sy opregulering in die teenwoordigheid van AS. Die fenotipiese “microarray” data stel voor dat Hst6p nodig is vir beskering teen stress en konfensiolele stresstoetse beaam. ΔΔhst6 was sensitief vir osmotiese, oksidatiewe, selwand- en swaar metaal stress. Omdat AS sensitiwiteit vir stress kan veroorsaak, stel die fenotipiese data voor dat HST6 opgereguleer was gedurende As blootstelling as ‘n response op stress. Benewens HST6 was ander ABC transport gene, wat ook blenagrik is in stress, ook opgereguleer. Ander groepe het onlangs die rol van hierdie proteïene in stress by hoër organismes soos mense ondek. Dit blyk dus dat die ABC-stressrespons wyd gekonserveerd is. ‘n Verdere funksie van Hst6p was onderdrukking van hifevorming onder toestande met oormaat stikstofbronne. ΔΔhst6 was filamentagtig onder hierdie toestande. ΔΔhst6 het ook geplooide kolonies met filamnetagtige kante gevorm, waarvan di selle filamntagtig was, onder stikstofstress. Dus ondersteun ons data die feit dat Hst6p in alle seltipes van C. albicans uitgedruk word en ‘n meer generiese rol speel as bloot feromoontransporter. Analyse van fenotipes het di took duidelik gemaak dat die aminosuursensor, Ssy1p, ook addisionele funksies het. Volgens literatuur, aktiveer Ssy1p die slyting van Stp1p en Stp2p in respons tot laer pH en voedingstofgebrek. Op hulle beurt aktiveer hierdie proteïene aminosuurpermeases, Mep1p en Mep2p, wat nodig is vir neutralisering van die pH en oorskakeling van gisagtige na filamentagtige groei, onderskeidelik. Ons het gevind dat Ssy1p lei tot differnsiële stressresponse onder stressvolle toestande. Terwyl die selle van die wilde tipe byvoorbeel opgeblase was, het die selle van ΔΔssy1 normaal gegroei op hoë ammonium konsentrasies en in teenwoordigheid van stikstofstress. ΔΔssy1 was ook weerstandbieded teen osmotiese en selwandstress. ΔΔssy1 was egter sensitief vir sittestress by 37 °C en 42 °C. Aangesien omskakeling van AS na PGE2 teen 37 °C uitgevoer was en blootstelling aan hierdie vetsuur kan lei to stress wat membraanvloeibaarheid kan beïnvloed, voer on aan dat SSY1 opgereguleer is in response tot o.a. hittestress. Alhoewel die transkripsie-analise nie gene wat direk betrokke was by PGE2 produksie, kon aantoon nie, het die analise van die wit-grys-ondeursigtig-tipe omskakeling, voorgestel dat opregulering van ORF19.4612 nodig was vir die vorming van growwe pienk selle en omskakeling van AS na PGE2. By 37 °C in RPMI-1640 medium, vorm die growwe pienk selle van die wilde tipe beduidend meer PGE2 vanaf AS. Δorf19.4612 vorm minder growwe pienk selle na 3 dae onder toestande soortgelyk aan die van RPMI-1640 medium. Aangesien ORF19.4612 uitgedruk was na 48 by 37 °C, word dit geimpliseer in wit-grys-ondeursigtig-tipe omskakeling en PGE2 produksie.
Thesis (Ph.D. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2015
Keywords: Candida albicans; Nutrient sensing; Phenotypic switching; PGE2 production; Pathogen; Stress response; Candida albicans -- Genetics; Human genetics